Rebranding museum tourism in Bali: A strategic destination branding model for engaging gen Z tourists - Prasiasa, Dewa Putu Oka; Subadra, I Nengah; Widari, Dewa Ayu Diyah Sri (International Journal of Innovative Research and Scientific Studies, 2025)
This study examined the declining visitation rates at museums in Bali and proposed a strategic destination branding model to engage Gen Z tourists. Grounded in an interpretivist paradigm, the research synthesized the theoretical lenses of the tourist gaze, storynomics tourism, and event tourism to develop its inquiries and strategic framework. Employing a qualitative approach, the study analyzed key tourism components, including attractions, accessibility, amenities, and ancillary services, to ensure alignment with Gen Z’s expectations and travel behaviors. The findings underscored the critical need to enhance core tourism elements to meet the experiential and digital preferences of this demographic. The proposed destination branding model integrated strategic segmentation, targeting, and positioning to create authentic and dynamic experiences that resonated with Gen Z’s values and aspirations. This study contributed to the discourse on cultural tourism and offered insights for museum operators and policymakers to advance destination branding strategies tailored to digitally native tourists and ensure the relevance and sustainability of museum tourism in Bali.